Analisis Keberlanjutan Kambing Etawa di Desa Tunggul, Paciran, Lamongan - Nabilah Ainur Rohmah; Wahyu Santoso; Mirza Andrian Syah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The Etawa goat agribusiness has significant economic potential for coastal communities, but the sustainability of the business is often influenced by limited resources and the social dynamics of the farmers. This study analyzes the sustainability level of the Etawa goat milk agribusiness in Tunggul Village from an ecological and social perspective as two fundamental aspects that determine business stability. Data were collected from 40 farmers and analyzed using RAP-Kagot-based Multi-Dimensional Scaling (MDS). The results show that the ecological dimension has a sustainability index of 68.64%, while the social dimension has an index of 65.37%, both of which are classified as moderately sustainable. The most sensitive attributes affecting sustainability include waste management, climate change, and disease management in the ecological dimension, while community conflicts and farmer education levels dominate the influence on the social dimension. These findings confirm that the sustainability of Etawa agribusiness does not only depend on technical aspects of production, but is also influenced by social capacity, access to information, and adaptation to environmental changes. The research recommendations emphasize the need to strengthen business management, improve the quality of farmer human resources, and integrate ecological and social approaches to promote a more adaptive and competitive dairy goat agribusiness.